2020
DOI: 10.1101/2020.04.18.047811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of predator foraging in response to prey infection favors species coexistence

Abstract: Article Keyword: Adaptive foraging, virulence, vulnerability, predator diet, profitability, parasitism Running title: Prey-infection induce diet evolution Number of words: 4 470 List of elements: Article (23p) with 1 table and 5 figures. Appendix (4p) with 2 figures. AbstractAs acknowledged by Optimal Foraging theories, predator diets depend on prey profitability.Parasites, ubiquitous in food webs, are known to affect simultaneously host vulnerability to predation and host energy contents, thereby affecting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Higher mortality also results in a reduction in competitive ability (Decaestecker et al 2015). While the evolutionary investigations of predator diet go beyond the scope of the present article, theoretical work suggests that parasite effects could lead to antagonistic modifications in predator diet: the increase in host vulnerability should favor predation on the host contrary to the increase in host mortality (Prosnier et al 2020). It would be interesting to perform experiments with and without infection dynamics, that is, by fixing or not fixing the host density or parasite prevalence to separately consider the effects on host energy and host availability.…”
Section: Discussionmentioning
confidence: 99%
“…Higher mortality also results in a reduction in competitive ability (Decaestecker et al 2015). While the evolutionary investigations of predator diet go beyond the scope of the present article, theoretical work suggests that parasite effects could lead to antagonistic modifications in predator diet: the increase in host vulnerability should favor predation on the host contrary to the increase in host mortality (Prosnier et al 2020). It would be interesting to perform experiments with and without infection dynamics, that is, by fixing or not fixing the host density or parasite prevalence to separately consider the effects on host energy and host availability.…”
Section: Discussionmentioning
confidence: 99%
“…Like in this study, reductions in prey density correspond to lower consumption rates by the predator, which ultimately favors prey persistence. Prosnier et al (2020) modeled parasite transmission as horizontal between prey. This is not the case for stickleback prey, which become infected by parasites through consumption (Barber and Scharsack 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known, for example, about the dual effects of parasite dynamics and predator evolution on coexistence of a predator with two competing prey. Prosnier et al (2020) used an epidemiological framework to examine the effect of prey infection on predator diet. They also examined the effect of predator diet evolution on coexistence using an adaptive dynamics evolutionary framework and showed that this type of evolution generally promotes coexistence among a predator and an infected and uninfected prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, we need improve our understanding of how food web dynamics play a role in the dynamics of trophically transmitted parasites, and future theoretical studies should incorporate the dynamics of parasites along with the dynamics of the community in which they reside. Prosnier et al (2020) used an epidemiological framework to examine the effect of prey infection on predator diet. They also examined the effect of predator diet evolution on coexistence using an adaptive dynamics evolutionary framework and showed that this type of evolution generally promotes coexistence among a predator and an infected and uninfected prey.…”
Section: Discussionmentioning
confidence: 99%